Current status and developmental trend on leakage and dispersion research for hydrogen-blended natural gas pipeline - Hongye JIANG; Mingyue KOU; Kexi LIAO; Taolong XU; Youlyu LI; Guoxi HE (You-qi chuyun)
Objective The practice of blending hydrogen into natural gas at specific proportions for pipeline transmission serves as a viable strategy for fostering a low-carbon economy and tackling the consumption challenges linked to surplus renewable energy generation. Hence, guaranteeing the safe operation of hydrogen-blended natural gas pipelines is significant to energy development. Methods To offer valuable insights into the proactive response to the development requirements of hydrogen-blended natural gas pipelines, this paper presents a comprehensive review of pertinent literature, spanning from 2009 to the present, based on the Cite Space software. It elaborates on the trajectories of leakage and dispersion within the hydrogen-blended natural gas pipeline context, emphasizing key research areas within this particular domain. The research status was examined regarding the application scenarios of these pipelines, categorized into two groups: confined spaces (such as kitchens and restaurants; block valve stations and other stations; utility tunnels and other tunnels) and unconfined spaces (including overhead, buried, and submarine pipelines). Various application scenarios were scrutinized to investigate research methodologies, patterns of leakage and substance accumulation, dispersion regularities, and associated influencing factors respectively. Furthermore, this paper offers recommendations on future research directions, aligning with industry trends and advancements in technical research. Results Despite a delayed initiation, research on the leakage and dispersion of hydrogen-blended natural gas pipelines in China has progressed rapidly. In comparison to unconfined spaces, confined spaces provide more favorable conditions for the accumulation of hydrogen-blended natural gas and the formation of explosive gas mixtures. In terms of research methodologies, numerical simulation approaches were found predominant in the studies within this field. Theoretical studies based on molecular dynamics were seldom conducted, and experiments were noted to be incongruent with the actual operation of pipelines. In terms of research directions, there is currently a lack of simulation studies focusing on certain typical hydrogen application environments. Moreover, there is a need for further advancement in research related to monitoring and detecting leakage and dispersion on hydrogen-blended natural gas pipelines. Conclusion Based on the study findings, recommendations include intensifying full-scale multi-field coupling experiments, expanding research on the leakage and dispersion characteristics of submarine and pressurized hydrogen-blended natural gas pipelines, concentrating on leakage and dispersion monitoring and detection techniques for hydrogen-blended natural gas pipelines, and developing practical methods for quantitative risk assessment and safety evaluation. These efforts collectively aim to provide technical underpinning for the development of specific standards and regulatory policies governing the pipeline transmission of hydrogen-blended natural gas.